Simple febrile seizures in toddlers: Do they have low serum calcium levels? - Sudhanshu Tiwari; K M Adhikari; Sandeep Dhingra (Indian Journal of Child Health, 2021)
Objective: The objective of the study was to study the serum calcium levels at presentation in two subgroups of febrile toddlers; one with and the other without febrile seizures. Materials and Methods: This observational, cross-sectional study was conducted in a tertiary care center. The mean serum calcium level was compared at presentation between the two subgroups of febrile toddlers; one group with and the other without febrile seizures during the presentation for current illness. Based on a previous study of micronutrients in febrile seizures and a pilot study from our center, a sample size of 35 toddlers in each group was included in the study. Main outcome measure was to see the number of children with serum calcium less than 9 mg/dl in each group and compare the proportions for any significant difference. Results: Serum calcium levels of less than 9 mg% was seen in 13 (37.1%) toddlers who presented with febrile seizures compared to the group of febrile toddlers without seizures 7 (20%). The difference was statistically significant (p